2011
DOI: 10.1073/pnas.1109438108
|View full text |Cite
|
Sign up to set email alerts
|

Affinity maturation of human CD4 by yeast surface display and crystal structure of a CD4–HLA-DR1 complex

Abstract: Helper T-cell activation generally requires the coreceptor CD4, which binds MHC class II molecules. A remarkable feature of the CD4-MHC class II interaction is its exceptionally low affinity, which ranges from K D = w200 μM to >2 mM. Investigating the biological role of the much lower affinity of this interaction than those of other cell-cell recognition molecules will require CD4 mutants with enhanced binding to MHC class II for testing in models of T-cell development. To this end, we used in vitro-directed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 28 publications
5
64
0
Order By: Relevance
“…To confirm that this measurement was reliable we established a binding assay wherein, in a highly multivalent form, sCD4 binding to cell-expressed pMHC II could be detected. Using this assay we confirmed that for native CD4 the binding site on pMHC II corresponds to that suggested by crystal structures of cross-species and affinity-matured CD4/pMHC II complexes (5,6). It can therefore be assumed that native CD4 forms the same "v-shaped" complex that affinity-matured CD4 forms with TCR/pMHC II, wherein contact with the TCR is seemingly precluded (19).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…To confirm that this measurement was reliable we established a binding assay wherein, in a highly multivalent form, sCD4 binding to cell-expressed pMHC II could be detected. Using this assay we confirmed that for native CD4 the binding site on pMHC II corresponds to that suggested by crystal structures of cross-species and affinity-matured CD4/pMHC II complexes (5,6). It can therefore be assumed that native CD4 forms the same "v-shaped" complex that affinity-matured CD4 forms with TCR/pMHC II, wherein contact with the TCR is seemingly precluded (19).…”
Section: Discussionsupporting
confidence: 58%
“…CD4 comprises two pairs of V-set and C2-set Ig superfamily domains, with early mutational data showing that the "top" two domains bind pMHC II (4). Crystal structures of cross-species and affinitymatured CD4/pMHC II complexes suggest that CD4 binds a pocket formed by the α2 and β2 domains of pMHC II (5,6). The role of coreceptors in heightening T-cell responses is well established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of these variants, which contains two substitutions in CD4 D1 (Gln40Tyr/ Thr45Trp), was produced as a full-length ectodomain (CD4 D1-D4) by secretion from baculovirus-infected insect cells. This CD4 mutant bound HLA-DR1 with K D = 8.8 μM, compared with no detectable binding for wild-type CD4, even at concentrations up to 400 μM (27). The CD4 mutant exhibited similar affinity for HLA-DR4 (K D = 10.1 μM), as measured by surface plasmon resonance (SPR) (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Indeed, the affinity of the pMHC-CD4 interaction, the dissociation constant (K D ) of which has been variously estimated to range from ∼200 μM to >2 mM (13,26), is even weaker than that of most TCR-pMHC interactions (1-100 μM) (13). To overcome this difficulty, we used in vitro-directed evolution by yeast surface display to increase the affinity of human CD4 for the MHC class II molecule HLA-DR1 (27). We subjected the CD4 D1 domain to in vitro random mutagenesis, and displayed the resulting mutant CD4 library on the yeast surface by fusion to agglutinin protein Aga2p.…”
Section: Resultsmentioning
confidence: 99%